Techniki wizualizacji tekstu z wykorzystaniem chmur znaczników i drzew znaczników - Dudek, Andrzej (Text Visualization Techniques with the Use of Tag Clouds and Tree Clouds, 2009)
Traditional data visualization techniques in a widely-mentioned multivariate statistical analysis require input in form of numerical data, most often - data matrices. The visualization of text data has never been considered in literature of subject and wording "text visualization" has been treated as an oxymoron. The situation has changed due to the expansion of the Internet and growing in exponential rate, number of world-wide-web pages. In the last few years such techniques as tag clouds, word clouds and tree clouds have appeared and gained a rapid popularity. In the article, creation of tag clouds, tag trees and tree clouds algorithms are described along with the various forms of tag clouds realization examples. The main areas of the usage of those techniques in marketing research are also proposed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 85-92